Close-Range 3D Collision Prediction under Attitude Uncertainty for On-Orbit Servicing Missions. Issue 17 (2016) - Posch, A.; Fuchs, B.; Renkl, J.; Sommer, J.; Schwientek, A.O.; Fichter, W.
Abstract: With a large and increasing number of satellites, not least because of expected falling prices due to new private space companies entering the market, the number of space assets requiring on-orbit maintenance is rising faster than ever. Advanced safety concepts which prevent collision between servicer and potentially valuable client spacecrafts in case of loss-of-control of the servicer spacecraft are necessary. Prediction of collision probability based on current state and navigation uncertainty is essential for safety evaluationand validation. An algorithm for prediction of the collision probability for the close range phase of satellite rendezvous is presented in this paper. 3d satellite geometry, relative attitude and relative position information and state uncertainty are taken into account during the calculation, resulting in an accurate and conservative collision probability estimate.